Sanitation in informal settlements in East Africa (3ksan) - Katrina J. Charles; Kenan Okurut; Aime Tsinda; J.M. Adogo; Pamela Abbott; L. Okotto; Robinah Kulabako; T. Kaime; Jonathan Chenoweth; R. Malcolm; S. Pedley (2013)
Improving access to sanitation in slums in East Africa is a challenge. The 3ksan project has been working to identify the barriers and catalysts to sanitation in Kigali, Kampala and Kisumu. Household surveys in the informal settlements in these three cities have provided insight into the different levels of service provision and demand, access to financial services, and perceptions of enforcement of the regulations. This paper presents key results from the household survey, highlighting the different challenges in the three cities.